Short-term exposure to benzalkonium chloride in bacteria from activated sludge alters the community diversity and the antibiotic resistance profile - Chacón Jiménez, Luz María (2021)
The continuous introduction of cleaning products containing benzalkonium chloride (BAC) from household discharges can mold the microbial communities in wastewater treatment plants (WWTPs) in a way still poorly understood. In this study, we performed an in vitro exposure of activated sludge from a WWTP in Costa Rica to BAC, quantified the changes in intI1, sul2, and qacE/qacEΔ1 gene profiles, and determined alterations in the bacterial community composition. The analysis of the qPCR data revealed elevated charges of antibiotic resistance genes in the microbial community; after BAC’s exposure, a significant increase in the qacE/qacEΔ1 gene, which is related to ammonium quaternary resistance, was observed. The 16S rRNA gene sequences’ analysis showed pronounced variations in the structure of the bacterial communities, including reduction of the alpha diversity values and an increase of the relative abundance of Alphaproteobacteria, particularly of Rhodospseudomonas and Rhodobacter. We confirmed that the microbial communities presented high resilience to BAC at the mg/mL concentration, probably due to constant exposure to this pollutant. They also presented antibiotic resistance-related genes with similar mechanisms to tolerate this substance. These mechanisms should be explored more thoroughly, especially in the context of high use of disinfectant.